Agency Problems at Dual-Class Companies - MASULIS, RONALD W.; WANG, CONG; XIE, FEI (Journal of Finance, 2009)
Using a sample of U.S. dual-class companies, we examine how divergence between insider voting and cash flow rights affects managerial extraction of private benefits of control. We find that as this divergence widens, corporate cash holdings are worth less to outside shareholders, CEOs receive higher compensation, managers make shareholder value-destroying acquisitions more often, and capital expenditures contribute less to shareholder value. These findings support the agency hypothesis that managers with greater excess control rights over cash flow rights are more prone to pursue private benefits at shareholders’ expense, and help explain why firm value is decreasing in insider excess control rights.